If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 1 + 2 = 3 Reorder the terms: 1 + 2 + c = 3 Combine like terms: 1 + 2 = 3 3 + c = 3 Add '-3' to each side of the equation. 3 + -3 + c = 3 + -3 Combine like terms: 3 + -3 = 0 0 + c = 3 + -3 c = 3 + -3 Combine like terms: 3 + -3 = 0 c = 0 Solving c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Simplifying c = 0
| -2x+4=-2+x | | 17-3n= | | 3(2w+8)=60 | | 3+4x=12+6x | | 17-(4m+4)=2+2m-19 | | -7x^6-14x^5+245x^4= | | 36x^2+2.44948974278x-1=0 | | 5x-2=3x-14 | | 10y+1=3(-2y-5) | | 3(z-21)=39-3(z-2) | | 36x^2+2.44948974278-1=0 | | 7w=4w+24 | | 120-3x=15x+18 | | 12f-4=7+f | | a^2-6af-27f^2= | | 7y^3+14y^2=0 | | 3x+1=-x+21 | | 8(3.5)=r | | x^2+25x+35=0 | | 3x+4+2=x-11 | | -13a=h | | 6x^2-54x+24=0 | | -3(14+6)-(-10-4x)= | | 16n=2+15n | | 2x+5=38 | | 5a^2-6a-32=0 | | -3b=42 | | w^2+3w-28= | | 1039-750=c | | 14.2t-25.2=3.8y+26.8 | | 2-3(x+2)=5x-12 | | 1/5(5p+10)=3p-4 |